Fintech and Its Impact on Banks : Systematic Literature Review - Rajapathirana, Jayani (2023)
This study targets at providing a systematic literature review about the probable impact of Fintech and its associated uses on the banks in a global perspective. This study aims to review the literature to recognize the applicable advantages, the challenges which the Fintech firms could possess for the conventional system of banking. Financial services have altered significantly over the last few generations, owing primarily to advances in technology in telecommunications, information and technolo-gy, and banking policies. Technological advancements prompted innovative strategies that altered a range of different products, services, production methods, and institution-al arrangements. Since some banks around the world continue providing antiquated, expensive, and time-consuming banking sectors, Fintech companies are capitalizing on the chance to just provide some many important functions of conventional banking that rely on innovative technology as a way to differentiate themselves Fintech businesses are creating pragmatic methods to improve the banking industry. The Fintech wave is backed by an assortment of offerings that appear to be less dedicated to marketing in-ventive financial products and much more centered on customers, allowing fast access to an extensive array of reasonably priced and incorporated financial products. The in-troduction of electronic advancements and their apparent effect on financial service sec-tor increases study desire to investigate the phenomenon. The research used a systematic literature review as the method of the study and the materials or sources it were selected from seven databases like Scopus, Bank of In-ternational Settlements (BIS), OECD iLibrary, IEEE Xplore, and National Bureau of Eco-nomic Re-search (NBER), Springer Link, and Research Gate. The ultimate research sam-ple was 23 articles from the years of 2009 to 2022. The major observations were themed and analyzed via the narrative synthesis methodology. According to the results ob-tained from the study, Fintech firms are making inroads and capturing the share of the market that was once dominated by traditional banks. Whereas, they are not expected to completely overshadow by banks. However, their presence drives enhancement in the performance of banks by fostering competition and pushing for advancement in tech-nology and customer service. It is proposed in the pertinent literature that the innova-tions of Fintech innovations in lending might have a substantial function in removing the shortcomings of the credit market by alleviating knowledge variances for customers and forming knowledge spill overs to conventional banking systems.